2018
DOI: 10.1002/jsfa.9383
|View full text |Cite
|
Sign up to set email alerts
|

The application of FT‐NIRS for the detection of bruises and the prediction of rot susceptibility of ‘Hass’ avocado fruit

Abstract: BACKGROUND A rapid non‐destructive in‐line grading system that can rapidly and accurately assess individual avocado fruit for internal quality attributes, including bruises and rots, would allow the avocado industry to provide a more consistent fruit quality to the consumer, optimise market distribution and ensure maximum yield for the producer and retailer. Fourier transform–near‐infrared (FT‐NIR) spectroscopy was investigated to detect bruises and rot susceptibility as an indication of shelf‐life in avocado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These investigations span from 2002 to 2020. Other studies have demonstrated NIRS applications for the detection of bruises and the prediction of rot susceptibility in 'Hass' avocado fruit [34]. The progression of ripening has been monitored using NIRS to assess issues related to fruit transpiration [35], as well as postharvest classification strategies during avocado ripening, categorizing it by maturity stages based on firmness [36].…”
Section: Application Of Different Nirs Scans By Fruit In Maturity Mon...mentioning
confidence: 99%
“…These investigations span from 2002 to 2020. Other studies have demonstrated NIRS applications for the detection of bruises and the prediction of rot susceptibility in 'Hass' avocado fruit [34]. The progression of ripening has been monitored using NIRS to assess issues related to fruit transpiration [35], as well as postharvest classification strategies during avocado ripening, categorizing it by maturity stages based on firmness [36].…”
Section: Application Of Different Nirs Scans By Fruit In Maturity Mon...mentioning
confidence: 99%
“…Traditional methods for assessing fruit and vegetable maturity, such as compression and puncture tests, have been widely used but are destructive and compromise the profitability of produce [ 5 , 6 ]. With technological advancements, a range of non-destructive techniques, including haptics [ 7 , 8 ], machine vision [ 9 , 10 ], visible and near-infrared spectroscopy (Vis/NIR) [ 11 , 12 ], hyperspectral imaging [ 13 , 14 ], electronic noses (e-noses) [ 15 , 16 ], and magnetic resonance imaging (MRI), now facilitate comprehensive maturity detection without damage [ 17 , 18 ]. These methods enable the evaluation of both internal and external fruit characteristics, offering insights into multiple quality parameters simultaneously.…”
Section: Introductionmentioning
confidence: 99%